2022
DOI: 10.1063/5.0088838
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effect of high-temperature storage on sulfide-based all-solid-state batteries

Abstract: The all-solid-state battery (ASSB) has become one of the most promising next-generation battery systems, since the aspect of safety has emerged as a crucial criterion for new large-scale applications such as in electric vehicles. Despite the recent remarkable progress in the performance enhancement, the real-world implementation of the ASSB still requires full comprehension/evaluation of its properties and performance under various practical operational conditions. Unlike batteries employed in conventional ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In all-solid-state batteries (ASSBs), the issues associated with volumetric change of CAMs are more detrimental . In addition to cracking and fracture in cathode particles as in the LIB system, the so-called “breathing” cathodes cause the separation of the solid electrolyte and CAM and also endanger the structural integrity of the system in a volume-constrained and pressurized setup. , Therefore, the volumetric change of the cathode has a significant effect on battery performance, such as long-term stability and discharge capacity, posing a great challenge for progress toward high energy density batteries. Therefore, it is desirable to employ cathode materials that undergo negligible volumetric changes upon Li insertion/extraction.…”
Section: Introductionmentioning
confidence: 99%
“…In all-solid-state batteries (ASSBs), the issues associated with volumetric change of CAMs are more detrimental . In addition to cracking and fracture in cathode particles as in the LIB system, the so-called “breathing” cathodes cause the separation of the solid electrolyte and CAM and also endanger the structural integrity of the system in a volume-constrained and pressurized setup. , Therefore, the volumetric change of the cathode has a significant effect on battery performance, such as long-term stability and discharge capacity, posing a great challenge for progress toward high energy density batteries. Therefore, it is desirable to employ cathode materials that undergo negligible volumetric changes upon Li insertion/extraction.…”
Section: Introductionmentioning
confidence: 99%
“…The robust cycle attributes of these oxide ASSBs enabled us to explore what intrinsically causes capacity fading of cathode composites in ASSBs, an area where previous studies have been lacking. While earlier research conducted on sulfide- and halide-based ASSB has suggested that the cathode degradation primarily arises from the deterioration of the interface between CAM and solid electrolyte due to repeated volume change of CAM during cycle, we discover that residual stress on CAM unexpectedly plays a critical role in the cathode degradation in oxide-based ASSBs. It is proposed that the cosintering of two oxides results in significant thermal mismatch during cooling, and this residual stress exacerbates the mechanical degradation of both the interface and CAM itself during the electrochemical cycles.…”
mentioning
confidence: 59%
“…The recent development of portable devices, electric vehicles, and large-scale energy storage systems has significantly increased the demand for safer and more energy-dense batteries. All-solid-state batteries (ASSBs) utilizing sulfide-based electrolytes provide an ideal geometry to attain a higher energy density and improved safety compared with conventional lithium-ion batteries (LIBs) using flammable organic liquid electrolytes. …”
mentioning
confidence: 99%